Contemporary Research on Management and Business: Proceedings of the International Seminar of Contemporary Research on Business and Management (ISCRBM 2021), 18 December 2021, Jakarta, Indonesia - Siska Noviaristanti (CRC Press, 2023)
This book contains 74 selected papers presented at the 5th International Seminar of Contemporary Research on Business and Management (ISCRBM 2021), which was organized by the Alliance of Indonesian Master of Management Program (APMMI) and held in Jakarta, Indonesia on 18 December 2021. This online conference was hosted by the Master of Management Program of Indonesia University. This year, ISCRBM focused on research related to driving sustainable business through innovation. Business has had to deal with the Covid-19 pandemic, so a new approach towards managing business to survive competition is indispensable. Innovation is the key for all organizations in surviving in the new normal and beyond. The Seminar aimed to provide a forum for leading scholars, academics, researchers, and practitioners in the business and management area to reflect on the issues, challenges and opportunities, and to share the latest innovative research and best practices. This seminar brought together participants to exchange ideas on the future development of management disciplines: human resource, marketing, operation, finance, strategic management and entrepreneurship.
Keywords: 650; human resources; research on management; strategic management